Immigrants in school area: connections between intercultural citizenship and civic values - Krawczun, Natalia Branco Lopes (2020)
From the perspective of Spanish philosopher Adela Cortina when points to the existence of civic values, whose incorporation in institutional educational action is very important, this paper aims to propose a reflection about the contribution of values such as freedom, equality, dialogue, active respect, and solidarity to the experience of institutional education in the intercultural dimension. This paper shows relevance because it bases on the conception opposed to the oppression of different cultures that is presented by Adela Cortina and Paulo Freire. It also shows the possibility that a beneficial and healthy relationship can be built in the school space making effectively viable the right to education for migrants. In a first moment, this work will point data of the entrance of immigrants in Brazil and general guidelines of the Brazilian migratory policy regarding the access to the education. Next, from the perspective of Adela Cortina, the concept of intercultural citizenship and the conexion with educational action in the school space will be portrayed. Finally, through the punctual approach of civic values, a reflection will be established on the contribution that these values incorporated to the institutional educational action can offer to promote of fruitful conditions for the development of intercultural citizenship.